Sweltsa wui and Haploperla valentinae (Plecoptera: Chloroperlidae), two new stoneflies from Sichuan province, China - Stark, Bill P. (Illiesia, 2009)
Sweltsa wui sp. n. and Haploperla valentinae sp. n. are described from Balangshan Pass, Sichuan Province, and compared with known Asian species. The new Sweltsa species lacks a transverse process on tergum nine, an atypical character for this genus, and the posterior margin of male tergum nine is not strongly concave as in other Sweltsa species, consequently the generic assignment is considered tentative.
Keywords: entomologija; entomology; new records; vrbnice; nove vrste; Plecoptera; Chloroperlidae; Kitajska; Sweltsa; Haploperla; China